Conceptual Model of Siskamling Information System Integration in Smart Village Architecture: A Theoretical Analysis of Efficiency and Sustainability - Devi Perwitasari, Ika; Hendrawan, Jodi (International Journal Education and Computer Studies (IJECS), 2025)
This study develops a conceptual model for integrating the Siskamling (Community Security System) into the Smart Village architecture by combining three core theoretical dimensions—information system efficiency, socio-technological sustainability, and digital governance integration. Through a conceptual–theoretical approach, the research synthesizes multiple frameworks, including Information System Integration Theory, the DeLone and McLean IS Success Model, Socio-Technical Systems Theory, and the Digital Sustainability Framework. The model positions Siskamling as more than a digital security platform; it is conceptualized as a socio-technical subsystem that fosters citizen participation, transparency, and institutional collaboration in rural governance. The findings highlight that Smart Village success depends not only on technological infrastructure but also on how digital systems align with social participation and collective resilience. Efficiency in information systems enhances trust and engagement, which in turn sustains socio-technical adaptation and supports integrative smart governance. Theoretically, the model bridges technological and social dimensions in community-based digitalization, while practically, it provides a reference for policymakers and local governments to design participatory and sustainable digital governance strategies. Future research is encouraged to empirically validate this conceptual framework using mixed methods, integrating variables such as digital literacy, policy support, and infrastructure readiness to ensure broader applicability.